A highly specific microarray method for point mutation detection. (January 2008) - Baaj, Yasser; Magdelaine, Corinne; Ubertelli, Virginie; Valat, Christophe; Talini, Luc; Soussaline, Françoise; Khomyakova, Elena; Funalot, Benoît; Vallat, Jean-Michel; Sturtz, Franck G.
Improvements of microarray techniques for genotyping purposes have focused on increasing the reliability of this method. Here we report the development of a genotyping method where a microarray was spotted with stemloop probes, especially designed to optimize the hybridization specificity of complementary DNA sequences. This accurate method was used to screen for four common disease-causing mutations involved in a neurological disorder called Charcot-Marie-Tooth disease (CMT). Healthy individuals' and patients' DNA were amplified and labeled by PCR and hybridized on microarray. The spot signal intensities were 81 to 408 times greater for perfect compared with mismatched target sequences, differing by only one nucleotide (discrimination ratio) for healthy individual "homozygous" DNA. On the other hand, "heterozygous" mutant DNA samples gave rise to signal intensity ratios close to 1, as expected. The genotypes obtained by this method were perfectly consistent with those determined by direct PCR sequencing. Cross-hybridization rates were very low, resulting in further multiplexing improvements. In this study, we also demonstrated the feasibility of real-time hybridization detection of labeled synthetic oligonucleotides with concentrations as low as 2.5 nM.